The Role of Social Support Systems for Fatherless Late Adolescents at Nur Hidayah Islamic High School Girls’ Dormitory - M. Fudhla Zahida; Alfin Miftahul Khairi (Universitas Islam Negeri Madura, 2026)
Fatherlessness significantly impacts the emotional, social, and psychological development of adolescents. This study explores the subjective experiences of adolescent girls living in dormitories who grew up without the presence or involvement of a father figure. Employing a qualitative descriptive approach, the research involved three participants selected through purposive sampling, with data collected via in-depth interviews, observation, and documentation. Data analysis followed the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The results indicate that fatherlessness affects five key dimensions of involvement defined by Hart: economic provider, friend and playmate, caregiver, protector, and advocate. While the absence of a father leads to emotional emptiness, reduced security, and economic instability, participants demonstrated resilience by adapting through social support from mothers, peers, teachers, and dormitory supervisors. These figures served as alternative substitutes providing essential emotional warmth, guidance, and protection. Ultimately, this study emphasizes the necessity of a supportive boarding school environment and the vital role of educators and counselors in providing empathetic, spiritually-based assistance to adolescents navigating fatherlessness.